Investigating the Role of English Language as International Medium for Learning Medical Sciences - Abdelrahman Elyass Mohamed Abdelmajd; Hassan Mahill Abdallah Hassan (Yayasan Visi Intan Permata, 2017)
This paper aims to answer “To what extent English Language as International Medium can help for Learning Medical Sciences?